With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Zami : une nouvelle façon d'écrire mon nom - Lorde, Audre (Trois, 1998)
Biomythographie selon le terme forgé par l'auteure, ce roman autobiographique est le seul texte en prose de cette poétesse américaine lesbienne et figure majeure de l'afroféminisme. Son approche originale des luttes contre les oppressions a participé à fonder la notion d'intersectionnalité. Dans ce texte, elle retrace son parcours et le rôle des femmes qui ont croisé sa route.
Keywords: afro-féminisme; amériques; approches et analyses; intersectionnalité; inégalités; littérature; personnes lesbiennes; racisme; régions géographiques; sexisme; systèmes d'oppressions; états-unis

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Disponible en ligne: https://link-springer-com.proxy.bibliotheques.uqam.ca/article/10.1057/fr.1997.7
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Killing rage: ending racism - hooks, bell (Penguing Books, 1995)
"One of our country's premier cultural and social critics, bell hooks has always maintained that eradicating racism and eradicating sexism must go hand in hand. But whereas many women have been recognized for their writing on gender politics, the female voice has been all but locked out of the public discourse on race. Killing Rage speaks to this imbalance. These twenty-three essays are written from a black and feminist perspective, and they tackle the bitter difficulties of racism by envisioning a world without it"–Back cover.
Keywords: afro-féminisme; amériques; approches et analyses; féminismes noirs; justice sociale; racisme; régions géographiques; sexisme; systèmes d'oppressions; états-unis

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Méthodologie féministe pour les femmes et le développement : concepts, contextes et pratiques dans L'égalité devant soi: sexes, rapports sociaux et développement international - Dagenais, Huguette (L'égalité devant soi: sexes, rapports sociaux et développement international, 1994)
Section: ix, 352 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; féminisme décolonial; histoire et politique; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; sexisme; système colonial; systèmes d'oppressions; thématiques

Outlaw culture: Resisting representations - hooks, bell (Routledge, 1994)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amériques; approches et analyses; féminismes noirs; périodes historiques; racisme; représentations; représentations médiatiques; régions géographiques; sexisme; systèmes d'oppressions; états-unis

The Lesbian and gay studies reader - Abelove, Henry; Barale, Michèle Aina; Halperin, David M. (Routledge, 1993)
Rassemblant quarante-deux essais révolutionnaires, dont beaucoup sont déjà des classiques, The Lesbian and Gay Studies Reader fournit une introduction indispensable à l'état contemporain des études lesbiennes/gay, illustrant largement l'étendue, la portée, la diversité, l'attrait et puissance du travail actuellement réalisé dans le domaine. Présentant des essais d'éminents chercheurs tels que Judith Butler, John D'Emilio, Kobena Mercer, Adrienne Rich, Gayle Rubin et Eve Kosofsky Sedgwick, The Lesbian and Gay Studies Reader explore une multitude d'expériences sexuelles, ethniques, raciales et socio-économiques. . S'étendant sur des disciplines telles que l'histoire, la littérature, la théorie critique, les études culturelles, les études afro-américaines, les études ethniques, la sociologie, l'anthropologie, la psychologie, les classiques et la philosophie, cette anthologie retrace l'inscription des significations sexuelles dans toutes les formes d'expression culturelle. Représentant le meilleur et le plus important travail en langue anglaise dans le domaine, The Lesbian and Gay Studies Reader aborde des sujets tels que les rôles butch-fem, la construction culturelle du genre, le séparatisme lesbien, la théorie féministe, le sida, l'éducation sexuelle sans risque, le colonialisme, le S /M, Oscar Wilde, Gertrude Stein, les livres pour enfants, le nationalisme noir, les films populaires, Susan Sontag, le placard, l'homophobie, Freud, Sappho, les médias, les hijrasde l'Inde, Robert Mapplethorpe, et la politique de représentation. Il contient également un essai bibliographique détaillé qui fournira aux lecteurs un guide inestimable pour des lectures complémentaires. Contributeurs :Henry Abelove, Tomas Almaguer, Ana Maria Alonso, Michele Barale, Judith Butler, Sue-Ellen Case, Danae Clark, Douglas sertissage, Teresa de Lauretis, John D'Emilio, Jonathan Dollimore, Lee Edelman, Marilyn Frye, Charlotte Furth, Marjorie Garber , Stuart Hall, David Halperin, Phillip Brian Harper, Gloria T. Hull, Maria Teresa Koreck, Audre Lorde, Biddy Martin, Deborah E. McDowell, Kobena Mercer, Richard Meyer, DA Miller, Serena Nanda, Esther Newton, Cindy Patton, Adrienne Rich, Gayle Rubin, Joan W. Scott, Daniel L. Selden, Eve Kosofsky Sedgwick, Barbara Smith, Catharine R. Stimpson, Sasha Torres, Martha Vicinus, Simon Watney, Harriet Whitehead, John J. Winkler, Monique Wittig et Yvonne Yarbro -Bejarano
http://bvbr.bib-bvb.de:8991/exlibris/aleph/a23_1/apache_media/DLCIQ4G6YQGKSDIDV2CF3NB8T7FQBI.pdf
Keywords: approches et analyses; corps; cours; discours dominant; histoire et politique; hétérosexisme; lesbianisme; outils; ouvrages de références; racisme; santé; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; violences

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (University of North Carolina Press, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Disponible en livre numérique et en format imprimé.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Sororophobia: Differences among women in literature and culture. - Michie, Helena (Oxford University Press, 1992)
This book looks at how differences among women have been textually represented at a variety of historical moments and in a variety of cultural contexts, including Victorian mainstream fiction, African-American mulatto novels, late twentieth-century lesbian communities, and contemporary country music. Sororophobia designates the complex and shifting relations between women's attempts to identify with other women and their often simultaneous desire to establish and retain difference. Michie argues for the centrality to feminism of a paradigm that moves beyond celebrations of identity and sisterhood to a more nuanced notion of women's relations with other women which may include such uncomfortable concepts as envy, jealousy, and competition as well as more institutionalized ideas of difference such as race and class. Chapters on literature are interspersed by "inter-chapters" on the choreography of sameness and difference among women in popular culture.
Keywords: approches et analyses; arts; classisme; discipline; histoire et politique; littérature; racisme; relations entre femmes*; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires

Frontiers: Selected essays and writings on racism and culture, 1984-1992 - Philip, Marlene Nourbese (Mercury Press, 1992)
Cette collection d'essais tant attendue se compose d'écrits sélectionnés parmi les nombreuses apparitions de la boursière Guggenheim Marlene Nourbese Philip dans des magazines, des journaux et des revues, y compris FUSE . Mordant, élégant, tour à tour farouchement interrogateur, magiquement lyrique et doucement explorateur, l'examen par Philip des questions contemporaines de race et de culture est toujours éloquent et impérieux.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; arts; cours; discipline; fem1000; inégalités; littérature; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty–and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Papers of the "Forth Hill Conference on Southern Culture", held at Clemson Univ. (1989). Textes de Fort Hill Conference on Southern Culture, tenue à Clemson University au printemps de 1989.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

Sisters in the struggle - Brand, Dionne; Stikeman, Ginny (1991)
Ce documentaire présente des femmes noires actives en politique ainsi que dans l'organisation communautaire, syndicale et féministe. Ils partagent leurs idées et leurs témoignages personnels sur le double héritage du racisme et du sexisme, liant leurs luttes personnelles à la bataille en cours pour mettre fin à la discrimination systémique et à la violence contre les femmes et les personnes de couleur.
Keywords: amériques; approches et analyses; canada; cours; fem3300; militance; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
https://nhfpl.kanopy.com/node/4694913
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Section: 236 p
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Dykewords: An anthology of lesbian writings - Lesbian Writing and Publishing Collective. (Women's Press, 1990)
An entertaining and refreshing anthology that includes writing about the vibration of lesbian love, cultural identity, sexual fantasy, overcoming alcohol abuse, a teenage coming out, lesbian history, imaginative lesbian antics for lesbian survival and much, much more
https://www.deslibris.ca/ID/412587
Keywords: anthologie; approches et analyses; corps; histoire et politique; identités LGBTQIA2+; littérature; outils; ouvrages de références; personnes lesbiennes; poésie; racisme; ressource en ligne; roman; santé; sexisme; sexualité; système colonial; systèmes d'oppressions; thématiques